Occupational and leisure-time physical activity decreases the odds of disability in older adults: prospective study - Dos Santos, Vanessa Ribeiro [UNESP] (2020)
Aging decreases physical function which can increase dependence in activities of daily living (ADL) and disability. However, physical activity (PA) may improve physical function and prevent disability in older adults. In addition, it is important to emphasize that research concerning the domains in which PA is practiced and the benefits for physical function of older adults is also important for the elaboration of preventative health measures for this population. Thus, the aim this study was to analyze the association of total PA and PA in different domains and odds of disability in older adults in a 24-month follow-up. The study included 211 older adults, aged ≥60 years (72±7 years, 72% women). Handgrip strength was measured using a digital dynamometer, gait speed and chair stand by functional tests. PA and dependence in ADL were self-reported. Older adults who remained sufficiently active in the occupational (OR:0.11;CI95%:0.01-0.93, OR:0.21;CI95%:0.07-0.69, and OR:0.13;CI95%:0.05-0.34) domain presented protection for high dependence in basic (BADL), instrumental (IADL) and advanced (AADL), respectively, as well as in total ADL (OR:0.25;CI95%:0.07-0.92). Older adults who remained sufficiently active in the leisure-time exercise (OR:0.28;CI95%:0.11-0.72, OR:0.44;CI95%:0.20-0.93 and OR:0.15;CI95%:0.04-0.49) domain presented protection for high dependence in IADL, AADL and total ADL, respectively. Moreover, older adults who remained sufficiently active in total PA (OR:0.11;CI95%:0.01-0.94, OR:0.30;CI95%:0.11-0.80 and OR:0.21CI95%:0.10-0.46) presented protection for high dependence in BADL, IADL and AADL, respectively, as well as in total ADL (OR:0.28;CI95%:0.09-0.86). The odds of disability are lower in older adults who are sufficiently active, especially in occupational and leisure-time exercise domains.